18fF-FDG PET/CT for Detection of Leukemic Transformation in Myelofibrosis. (June 2015) - Derlin, Thorsten; Clauditz, Till Sebastian; Kröger, Nicolaus
Abstract : Abstract: Myelofibrosis is a rare clonal hematopoietic stem cell disorder characterized by chronic myeloproliferation, atypical megakaryocytic hyperplasia, and potential leukemic transformation. We report a case of leukemic transformation detected by 18 F-FDG PET/CT. A 56-year-old woman with myelofibrosis and newly diagnosed space-occupying lesion of the chest wall underwent whole-body PET/CT for further evaluation. 18 F-FDG PET demonstrated marked tracer uptake within that lesion. Histopathological evaluation revealed myeloid sarcoma evidencing leukemic transformation. 18 F-FDG PET/CT is a valuable tool-enabling sensitive detection of leukemic transformation in myelofibrosis, particularly in case of extramedullary organ involvement.